Maternal migration issues in foreign countries: legal analysis and recommendations for Kazakhstan - Turysbekova, G.G.; Yessetova, S.K.; Kassymzhanova, A.A. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
The purpose of this study is to analyze the legal aspects of maternal migration abroad and develop recommendations for adapting Kazakhstan’s legislation to the realities of modern migration policy. The key idea is the need to develop a comprehensive approach to protecting the interests of mothers and their children in the context of migration. This article analyzes existing problems and proposes specific measures to improve legal regulation in Kazakhstan. The results of the study can be used in the development of new legislation and programs to support migrants. The study utilizes methods of comparative law, analysis of international treaties, and analysis of national legislation in foreign countries. The study identified gaps in Kazakhstan’s legislation related to the protection of the rights of migrant mothers. A comparative analysis of international experience is conducted, and specific recommendations for its adaptation to Kazakhstan’s conditions are proposed. This article contributes to the development of the theory and practice of migration law, proposing specific solutions for improving the legal protection of one of the most vulnerable categories of migrants. The results of this work can be used by government agencies, non-governmental organizations, and other stakeholders to develop and implement effective migration policies aimed at protecting the rights of migrant mothers and their children.